Factors Affecting Interest in Becoming a Sharia Insurance Participant (Study of Sharia Insurance Participants at Prudential Binjai Branch) - Arpin Dalimunthe; Yusrizal Yusrizal (Penerbit Jurnal Indonesia, 2022)
This research was made because of the increasing number of sharia insurance because sharia insurance is an effort to protect and help each other between a number of people or parties through investments in the form of assets that provide a pattern of return to face certain risks through contracts (commitments) that are in accordance with sharia. The results of the research conducted were descriptive qualitative research and used primary and secondary data. The writing method used by the author is a literature review. The literature review method is a method used to describe a finding or theory as material for further research that is obtained and used as reference material. The results obtained are the factors that influence the public's interest in becoming a participant in Sharia insurance at Prudential's Binjai branch.